1994
DOI: 10.1177/42.8.7913105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and storage in rat thyroid C-cells.

Abstract: Thyroid C-cells have the capacity to produce a variety of peptides, as do C-cell tumors. The cellular content of one such peptide, somatostatin, is restricted to a minority of C-cells in rat and human. We set out to clarify whether the synthesis of somatostatin is equally restricted and to study changes that occur in somatostatin synthesis with age. We used immunocytochemistry to localize somatostatin and calcitonin in conjunction with in situ hybridization, using digoxigeninlabeled oligoprobes to localize som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
(6 reference statements)
1
10
0
Order By: Relevance
“…The sequence was as follows: 5′‐ACAGGATGTGAATGTCTTCCAGAAGAAGTTCTTGCAGCCAGC‐3′. This probe has been previously shown to demonstrate SS mRNA in normal thyroid C cells and pancreatic islet (D) cells in the rat (Thomas et al . 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence was as follows: 5′‐ACAGGATGTGAATGTCTTCCAGAAGAAGTTCTTGCAGCCAGC‐3′. This probe has been previously shown to demonstrate SS mRNA in normal thyroid C cells and pancreatic islet (D) cells in the rat (Thomas et al . 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Thomas et al . (1994) first showed that only a small proportion of normal C cells in the rat are capable of producing and storing SS.…”
mentioning
confidence: 99%
“…Both antibodies against calcitonin and CGRP marked almost all of the C-cells in the mouse thyroid, even though CGRP immunoreactivity is not always detected in all thyroid C-cells in several animals, including the mouse (Zabel et al 1988;Arias et al 1989;Sawicki and Zabel 1999;Thomas et al 1994). The IHC co-localization of the convertases and calcitonin has also been reported in human medullary thyroid carcinomas, which contained elevated levels of these enzymes compared to normal thyroid C-cells (Tomita 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several ICC studies have demonstrated that C-cells are located not only in the thyroid but also in the parathyroid glands in some mammalian species (Kameda 1971). Moreover, several immunohistochemical (IHC) studies have detected calcitonin-gene related peptide (CGRP), derived as a splicing variant from a gene that also encodes calcitonin, in the C-cells of some laboratory rodents, including the mouse (Zabel et al 1988;Arias et al 1989;Wimalawansa 1991;Thomas et al 1994;Sawicki and Zabel 1999). Although the antiserum against CGRP does not always react against all of the C-cells, the expression of CGRP in C-cells is confirmed by a study using ISH techniques (van Lieshout et al 1995).…”
mentioning
confidence: 99%
“…Our study does not require this confirmation of CT presence in the counted secretory granules because it is well known that at least 99% of all Ccells in the adult rat thyroid contain CT [13][14][15]. Although present in the secretory granules of these cells are also other peptides (e.g., CT gene-related peptide, somatostatin, and neurotensin), they coexist with CT [13,16].…”
mentioning
confidence: 90%